Instrumentalizacja procesu legislacyjnego w carskiej Rosji i jej wpływ na specyfikę rosyjskiego systemu źródeł prawa - Smyk, Grzegorz (Czasopismo Prawno-Historyczne, 2018)
The legislative mechanism of the Russian Empire and related to it types and hierarchy of the sources of law has always been, and continues to be, a controversial issue, giving rise to numerous polemics. This is because the very essence of the autocratic rule in the Russian Empire makes it impossible to accurately distinguish between the legislative and the executive powers. The lack of transparency of the hierarchy of sources of law also means that every attempt the Russian theorists of state and administrative law make to identify and clarify those sources is always deemed to fail. The political transformations of 1906 did not bring any change to the existing system either as no compromise was ever possible in an autocracy in which, despite appearances of legality, the predominant drive was to ensure the integrity of the absolute power of the tsar. The characteristic feature of the legislation in the Russian Empire was its complexity and lack of clarity both with regards to the types and forms of the law sources and the way in which laws were made. As a result, in the all-powerful bureaucratic system of the Russian Empire, laws could be breached, violated or bent with impunity and without observance of any acceptable procedure, merely at the discretion of the sovereign.